If p(x) = 4 + 3x - x2 + 5x3, find: give the answer below please
(i) p(2)
Answers
Answered by
0
Answer:
Step-by-step explanation:
p(-2) = -46
p(x) = 4 + 3x - x² + 5x³
we get p(-2) by substituting -2 for each x in the formula:
p(-2) = 4 + 3×(-2) - (-2)² + 5×(-2)³
= 4 - 6 - 4 - 40
= -46
OR
p(2)= 4+ 3(2) - (2)² + 5(2)³
= 4 + 3x2 - 2x2 + 5(2x2x2)
= 4 + 6 - 4 + 5(8)
= 4 + 2 + 5x8
= 6 + 40
= 46 Ans
Answered by
0
Answer:
34
Step-by-step explanation:
The steps are in the above pic.
Hope this helps you....
Attachments:
![](https://hi-static.z-dn.net/files/d02/d090d975d0486266cc085ba56b055051.jpg)
Similar questions
Math,
1 month ago
Math,
1 month ago
English,
3 months ago
Computer Science,
11 months ago
English,
11 months ago
India Languages,
11 months ago